DIVINE PERSONS IN GENESIS: The Theological Implications - William D. Barrick (Scriptura Indonesia, 2020)
Beginning with its third word, the book of Genesis reveals that God (םיִהלֹ)ֱא exists and that He created the heavens and the earth. The seventeenth word from the end of the book is also “God” (םיִהלֹ)ֱא—in Joseph’s declaration that God will provide for the descendants of his father Israel. Few exegetes would argue today that the plural form of םיִהלֹ ֱא even implies a plurality of divine persons—and rightly so. However, evidence exists within the text of the first book of Moses that might indicate a distinction of persons in the Godhead. For example, both Genesis 1:2 and 6:3 seem to refer to the Spirit of God. Other statements in the text of Genesis appear to mention more than one divine person named Yahweh (19:24). Some references involve a person identified as the “angel/messenger of Yahweh” (e.g., 22:11). Was this individual the same as one of the “three men” who appeared to Abraham (18:2) and before whom Abraham stood (18:22)? Is he a person of the Godhead? In addition to these more direct and perhaps less abstract references to a divine person, Genesis includes several first person plural statements (“us” and “our”) spoken by a divine person (1:26; 3:22; 11:7). Are these references best explained as multiple divine persons, some sort of plural of majesty, or some council of spirit beings other than divine? What is the exegetical evidence? What are the implications theologically regarding either a plurality of divine persons or even a limitation to three such divine persons? Furthermore, how do these implications affect the way we understand ancient human conceptions of God, His person, His attributes, and His work from Adam to Joseph?